2018
DOI: 10.1089/cren.2018.0067
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Renal Cell Carcinoma with a Ureteral Thrombus

Abstract: Introduction: Cancers of the kidney, arising from either the renal parenchymal tissue or the renal pelvis, is among the 13 commonest types of malignancy globally, accounting for between 3% and 4% of all newly diagnosed cancers. Renal cell carcinoma (RCC) accounts for 85% of all malignant renal neoplasms. We present a rare case of an RCC directly extending into the renal pelvicalyceal system and with a thrombus within the ureter.Case Presentation: A 39-year-old woman presented with a long-standing history of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Following literature review, only six previous case reports have been identified. 27 These reports do however describe similar histological characteristics. All cases appear to involve extensive pelvicalyceal and renal sinus involvement with an absence of urothelial invasion.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Following literature review, only six previous case reports have been identified. 27 These reports do however describe similar histological characteristics. All cases appear to involve extensive pelvicalyceal and renal sinus involvement with an absence of urothelial invasion.…”
Section: Discussionmentioning
confidence: 61%
“…Direct intra-luminal spread down the ureter via the pelvicalyceal collecting system is an uncommon event published only in previous case reports. [2][3][4][5][6][7] Due to its uncommon nature, little is known regarding prognostic role of ureteric involvement of RCC, however urinary collecting system invasion has been shown to be significant. 8,9 This has resulted in pelvicalyceal invasion becoming included in the 2018 American Joint Committee on Cancer (AJCC) RCC staging classification as pT3a disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the investigation, renal tumor occupies the second place in the urogenital system tumors in China, only second to bladder cancer, accounting for nearly 2% adult cancers (Mlot, Szczylik, & Rzepecki, ). ccRCC is a highly metastatic tumor, accounting for about 85% of RCC (John, Aldera, Sinha, & Lazarus, ). Recently, targeted therapy became a promising treatment for ccRCC, and drugs on the basis of several therapeutic targets, such as BAP1 and PBRM1, have been demonstrated by clinical proof (da Costa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of RCC has risen steadily and it has the highest mortality (around 40%) among the genitourinary cancers. Its maximum incidence was reported in the sixth decade of life with more frequency in Afro-American people (1)(2)(3). Among men and women, this malignancy takes the tenth and fourteenth places, respectively (4).…”
Section: Introductionmentioning
confidence: 99%